Satunetra Development, Chat Therapy Applications Based on Artificial Intelligence for The Blind - Dwi Gusna; Uti Nur Salehah; Nurul Hidayah Zainal; Nurul Islamiyah; A. Azzahrah Ainun (Ridwan Institute, 2021)
Nowadays the level of people with disabilities is increasing, the fact is that the most people with disabilities in Indonesia are blind. Most of the blind people experience visual disturbances so that these limitations trigger mental instability and often experience discouragement, stress, anxiety, over-confidence and lack of confidence. Besides that, like normal humans, blind people also need the role of other people, they also need someone to be a friend or a substitute figure who can always accompany them. With the development of increasingly sophisticated technology, an artificial intelligence-based chat therapy application for the blind has a function as a friend as well as a psychological consultant. This study uses the Waterfall application development method. The application testing was carried out at one of the schools for children with special needs in Makassar, so that the results of the application could be seen whether it really was in accordance with the goals and needs. Therefore, the existence of this application makes it possible to foster motivation to have a return in living life even though in limited vision.